Role of weather on Alternaria leaf spot development in crucifers - and PRATIBHA SHARMA, R. SELVAMANI*, R.T.P. PANDIAN (Indian Phytopathology, 2014)
Black leaf spot caused by Alternaria brassicae (Berk.) Sacc. is an important disease of crucifers. Progression of Alternaria leaf spot was found to be influenced by environmental factors prevalent under field conditions. There was periodical increase in lesion number and per cent disease index (PDI). However, PDI increase varied with crops and crop varieties. PDI progression was higher in mustard varieties followed by cauliflower and cabbage. Highest area under disease progress curve (AUDPC) value was recorded on Pusa Bold variety of mustard and the lowest was recorded on CJ-182 variety of cabbage. On the contrary, maximum and minimum temperature was positively correlated with disease development, but average temperature showed high degree of correlation than the minimum (1.5-15.3°C) and maximum temperature (10-28°C). The laboratory study indicated that optimum conditions for spore germination were 20-24°C with more than 90 per cent relative humidity.